Bipolar catheter ablation in ventricular myocardium. Issue 1 (23rd December 2019) - Liu, Xiaolin; Chen, Qiushi; Fan, Baohan; Zhu, Wenwu; Zhao, Hongyan; Zhu, Yeqian; Zhao, Pengcheng; Zhang, Fengxiang; Kojodjojo, Pipin
Abstract: Background: Recurrence rates after catheter radiofrequency ablation (RFA) for arrhythmias arising from deep myocardial substrates can exceed 40%. Failure of RFA is in part due to the inability of widely used unipolar ablation (UA) to create transmural lesions capable of disrupting the critical components of the arrhythmia circuit. A radiofrequency generator was custom‐made to deliver bipolar ablation (BA) to test the hypothesis that BA is more effective compared to UA in achieving transmurality and to determine the optimal configuration for ventricular BA. Methods: Sequential UA and BA were created in porcine ventricular septal and free wall preparations using irrigated, contact‐force sensing ablation catheters, orientated perpendicularly to the myocardium. Return catheters, durations of ablation, irrigating fluids, and power settings were varied to determine the optimal configuration for BA. Lesion characteristics, transmurality, and occurrence of steam pops were analyzed. Results: In both ventricular septal and free wall models, BA resulted in significantly more transmural lesions while causing less steam pops ( P < .01). BA lesions were deeper, narrower but larger in volume. Use of 8 mm ground catheters in the epicardium resulted in overheating during BA with temperatures exceeding 95°C, limiting power delivery. Increasing duration and powers of BA resulted in progressively larger lesions and increased transmurality (all P < .01), and 0.45% saline as the irrigation did not enhance BA. Conclusion: BA created larger lesions with increased chances of transmurality but at lower risks of steam pops. Use of an irrigated catheter as the return electrode and 30 W of BA delivered over 120 seconds provides the optimal balance between creating deep, transmural lesions and avoiding steam pops.